Fatwa controls between Misyar marriage and polygamy: A critical analytical study - Bashir, Khawla Ghouri; Karadaghi, Arif Ali Arif; Al-Janabi, Adel Maarouf Laftah Younis (Journal of Islamic Sciences, 2021)
The researcher (female) takes to discussion the topic of “Fatwa regulations between Misyar (marriage where wife concedes some of her marriage rights) and polygamy marriages.” This is a critical and analytical study, which targets the perspectives of contemporary Islamic scholars who permit/not permit these marriages, their credible proofs along with their discussions, and the replies to them. It then presents legal regulations that make Misyar marriages a legal polygamy, along with unveiling its place in the Islamic Sharia’a (law) through results of surveying five Algerian women. The research ends with supporting the perspective of the contemporary scholars who are against Misyar marriages for it not achieving the overall interest of the public, not to mention other domains where it is also rejected due to its contradictions with Islamic laws. Thus, Misyar marriage can only be a modern model of for polygamy mentioned in the Quran and Sunnah.
Keywords: Fatwa controls; Misyar; polygamy; Sharia's purposes